Inflammatory lipid biomarkers and transplant-free mortality risk in hepatitis B-related cirrhosis and hepatic encephalopathy - Shi, Ke; Wang, Xiaojing; Yi, Zhang; Li, Yanqiu; Feng, Ying; Wang, Xianbo (Frontiers in Medicine, 2025)
ObjectiveInflammatory reactions and dyslipidemia are associated with the pathogenesis and prognosis of hepatitis B virus-related cirrhosis. We aimed to assess the predictive ability of these parameters in patients with hepatitis B virus-related cirrhosis and overt hepatic encephalopathy (HBV-related OHE).DesignWe conducted an analysis of 1,404 participants diagnosed with HBV-related OHE between January 2008 and July 2023. The prognostic significance of the neutrophil-to-high-density lipoprotein cholesterol (HDL-C) ratio (NHR), lymphocyte-to-HDL-C ratio (LHR), and monocyte-to-HDL-C ratio (MHR) was evaluated using the area under the receiver operating characteristic curve (AUC). Restrictive cubic splines (RCS) were employed to explore the relationship between NHR and 12-month transplant-free (TF) mortality. This study included a prospective test cohort of 328 patients.ResultsNHR was identified as an independent risk factor for 12-month TF mortality. The AUC for NHR (0.776) was similar to that of the model end-stage liver disease (MELD) score (AUC: 0.777). In the test cohort, NHR demonstrated AUC values comparable to MELD, with significantly higher AUCs than LHR and MHR (both p < 0.05). Based on cutoff values for NHR and MELD, patients were classified into four risk subgroups: very-low (NHR < 10 and MELD <18), low (NHR ≥ 10 and MELD <18), moderate (NHR < 10 and MELD ≥18), and high (NHR ≥ 10 and MELD ≥18). The 12-month TF mortality rates in the training cohort were 7.2, 23.5, 30.8, and 51.4%, respectively, for these subgroups, while in the test cohort, the rates were 8.7, 20.5, 30.7, and 46.0%.ConclusionNHR is a valuable and accessible prognostic indicator for 12-month TF mortality in patients with HBV-related OHE. Patients with both NHR ≥ 10 and MELD ≥18 are at the highest risk of mortality.